Pengaruh Kualitas Produk, Harga Dan Kualitas Layanan Terhadap Keputusan Pembelian Konsumen Pada Toko Nusantara Collection Padang - Elmes Santika; Maivalinda Maivalinda (Jurnal Ekonomi dan Bisnis Digital, 2025)
This study examines the influence of product quality, price and service quality on consumer purchasing decisions at the Nusantara Collection store. The study was conducted at the Nusantara Collection Store with a sample of 100 respondents. The method used in this study is a quantitative method with a descriptive approach. The data source used by the researcher is a primary data source using a data collection technique in the form of a questionnaire. Hypothesis testing used in this study is by multiple linear analysis with the IBM SPSS 23 Statistics tool. The results of the tests that have been carried out indicate that (1) product quality has a positive and significant effect on purchasing decisions, (2) price has a positive and significant effect on purchasing decisions, (3) service quality has a positive and significant effect on purchasing decisions, (4) product quality, price and service quality periodically have a positive and significant effect on purchasing decisions.